2004
DOI: 10.1557/proc-820-o9.8
|View full text |Cite
|
Sign up to set email alerts
|

From an Integrated Biochip Detection System to a Defensive Weapon Against the SARS-CoV Virus: OBMorph

Abstract: In this paper, an integrated multifunctional biochip detection system, which we call "OBMorph", are presented. This unique system integrates several optoelectronic-based biological diagnostic tools such as an ellipsometer, a laser Doppler vibrometer/interferometer, a SPR (surface plasmon resonance) analyzer, an interference microscope, a photon tunneling microscope, an optical coherence tomography unit and a confocal scanning microscope. This OBMorph system, useful as a powerful optical metrology diagnostic to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A thin layer of flash-frozen sample is scanned using low energy electrons to get a 2D image of the sampleResolution: 3.4 Å 3D reconstruction of the HCoV-NL63 spike glycoprotein trimmer Walls et al, 2016;Baker, 2018 Atomic force microscope (AFM) AFM works by scanning the sample surface with a cantilever probe to which a LASER is pointed to measure surface variationsWorking modes-tapping mode, contact mode, and noncontact modeResolution: up to 30 nm Study the surface ultrastructure of SARS-CoVObserve the changes in the cell membrane during the release of a virion particleStudy the absorption of SARS-CoV viral particles in biopolymeric vesiclesTo study the structure and size of spike proteins which is present in the viral coat Yang, 2004;Lin et al, 2005;Eaton & West, 2010;Ng et al, 2004;Ciejka, Wolski, Nowakowska, Pyrc, & Szczubiałka, 2017;Lee et al, 2004 Fluorescence Lichtman & Conchello, 2005;Wang et al, 2008;Lu, Liu, & Tam, 2008;Manopo et al, 2005;Yuan et al, 2006;Yuan et al, 2005;Knoops et al, 2008 novel coronavirus that was successfully isolated from patients with SARS and identified them using TEM. The oropharyngeal sample from the patient was inoculated into Vero E6 mammalian cell lines (Ksiazek et al, 2003).…”
Section: Electron Microscopy Visualization Of Sars-covsmentioning
confidence: 99%
“…A thin layer of flash-frozen sample is scanned using low energy electrons to get a 2D image of the sampleResolution: 3.4 Å 3D reconstruction of the HCoV-NL63 spike glycoprotein trimmer Walls et al, 2016;Baker, 2018 Atomic force microscope (AFM) AFM works by scanning the sample surface with a cantilever probe to which a LASER is pointed to measure surface variationsWorking modes-tapping mode, contact mode, and noncontact modeResolution: up to 30 nm Study the surface ultrastructure of SARS-CoVObserve the changes in the cell membrane during the release of a virion particleStudy the absorption of SARS-CoV viral particles in biopolymeric vesiclesTo study the structure and size of spike proteins which is present in the viral coat Yang, 2004;Lin et al, 2005;Eaton & West, 2010;Ng et al, 2004;Ciejka, Wolski, Nowakowska, Pyrc, & Szczubiałka, 2017;Lee et al, 2004 Fluorescence Lichtman & Conchello, 2005;Wang et al, 2008;Lu, Liu, & Tam, 2008;Manopo et al, 2005;Yuan et al, 2006;Yuan et al, 2005;Knoops et al, 2008 novel coronavirus that was successfully isolated from patients with SARS and identified them using TEM. The oropharyngeal sample from the patient was inoculated into Vero E6 mammalian cell lines (Ksiazek et al, 2003).…”
Section: Electron Microscopy Visualization Of Sars-covsmentioning
confidence: 99%
“…In this proof-of-concept design, the M13K07 bacteriophage was used as a model target. 179 Lee et al 180 described a unique system integrating several optoelectronic-based biological diagnostic tools such as an ellipsometer, a laser Doppler vibrometer/interferometer, SPR analyzer, an interference microscope, a photon tunneling microscope, an optical coherence tomography unit, and a confocal scanning microscope. This OBMorph system, useful as a powerful optical metrology diagnostic tool, can be used at the beginning of sensor chip fabrication, during the signal detection/monitoring, and in the final biological analysis.…”
Section: Optical Biosensorsmentioning
confidence: 99%
“…This OBMorph system, useful as a powerful optical metrology diagnostic tool, can be used at the beginning of sensor chip fabrication, during the signal detection/monitoring, and in the final biological analysis. 180 …”
Section: Optical Biosensorsmentioning
confidence: 99%
“…For our purposes, one example of the above-mentioned perceptual model of serendipity is our newly developed "OBMorph", a multi-functional bio-oriented microscope which was used to successfully create protective gear and facemasks for use against the SARS (Severe Acute Respiratory Syndrome) virus during the SARS crisis [22,23] in the early 2000s. The OBMorph work was also extended to create a paper speaker (FleXpeaker) [24] that won various awards.…”
Section: Serendipity Factor In Interdisciplinary Research For Smart Smentioning
confidence: 99%
“…The team also had an underlying belief that a world-class team must also assume social responsibility and focus on research that can benefit others. The interdisciplinary character of the research team and the team's dedication to pursuing socially-useful outcomes was later identified as the key serendipity factor which drove the successful research [22,23].…”
Section: Serendipity Factor In Interdisciplinary Research For Smart Smentioning
confidence: 99%